Perception of Wellness Factors of Working People in Housing Projects - Saensamran, Darin; Klinmalai, Siwaporn; Janjamlah, Tipsuda (Journal of Architectural/Planning Research and Studies (JARS), 2025)
Climate change and the COVID-19 pandemic have influenced wellness trends. The wellness condominium market in Thailand is expanding rapidly, with working people being the primary target demographic. This study aims to analyze the wellness factors of working people and to compare their perceptions of wellness between residents of vertical housing projects (condominiums) and those of horizontal housing projects (townhouses and single houses). Data were collected through a questionnaire administered to a sample of 123 working people and analyzed using Exploratory Factor Analysis. The analysis identified nine key wellness factors: 1) environment conducive to living, 2) mental balance, 3) openness to learning, 4) stability in work, 5) good relationship with co-workers, 6) good relationship with the community, 7) good health, 8) freedom to live, and 9) self-care from diseases. The findings indicate that overall, working people perceive good relationships with co-workers as the most important, while having good relationships with the community is seen as the least important factor impacting wellness. Variables that influence differences in wellness perceptions include housing project type and income. Working people in condominiums perceive wellness factors as more important than working people in townhouses, in the factors of environment conducive to living, good relationship with the community, and good health. Additionally, working people with incomes not exceeding 15,000 THB per month place less importance on wellness factors compared to those with incomes of more than 65,000 THB per month, in the factors of environment conducive to living, mental balance, openness to learning, stability in work, and good relationship with co-workers. Entrepreneurs, real estate developers, and designers can use the research findings to prioritize wellness factors in housing projects, addressing the diverse needs of different project types and income groups while fostering community engagement and sustainable practices.